Use of Complementary and Alternative Medicine in Patients With Idiopathic Inflammatory Demyelinating Diseases of the Central Nervous System: A Cross-Sectional Study in Thailand - Punchika Kosiyakul, MD; Jiraporn Jitprapaikulsan, MD; Natthapon Rattanathamsakul, MD; Sasitorn Siritho, MD; Onpawee Sangsai, MSc; Kamonchanok Aueaphatthanawong, BSc; Montira Engchuan, BNS; Naraporn Prayoonwiwat, MD (Elsevier, 2024)
Background: Complementary and alternative medications (CAM) are common among patients with multiple sclerosis (MS) for physical and psychological support. However, there is insufficient data regarding the application of CAM in the different cultures and beliefs of each community as well as patient's status. Objective: To evaluate the prevalence and modalities of the use of CAM among patients with central nervous system idiopathic inflammatory demyelinating diseases (CNS-IIDD) in a tertiary care hospital Methods: A cross-sectional study was conducted at Siriraj Hospital from June to December 2021 involving patients with MS, neuromyelitis optic spectrum disorders (NMOSD), myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD), idiopathic transverse myelitis (iTM), and optic neuritis (ON) to examine the prevalence and mode of CAM use and its correlation with patient characteristics. Results: There were 107 patients. The diagnoses were MS (38), NMOSD (55), MOGAD (5), iTM (7), and ON (2). Most of the patients were female (89.7%), and 61.7% were diagnosed over 5 years. The mean Expanded Disability Status Scale was 2.63 (S.D., 2.38), and the median ambulation index was 0 (range 0-8.5). There were 68 patients (63.6%) with a history of CAM use for at least 3 months, while those with current use decreased to 62 (58.5%). Vitamins and minerals were the most commonly used, particularly vitamin D (97.1%) and calcium (47.7%). Both treatments were primarily prescribed (95.3%) rather than self-administered (24.3%). The main reasons for the use of CAM were to strengthen their health (48.6%) and relieve existing symptoms (28.0%). Conclusions: The use of CAM is common among patients with Thai CNS-IIDD. Further exploration of patient perspectives and preferences regarding CAM usage may contribute to a more comprehensive management approach for patients with CNS-IIDD.